Management of CAR-T cell therapy in patients with multiple myeloma: a systematic review and expert consensus in Australia - Ho, P. Joy; Quach, Hang; Sidiqi, M. Hasib; Lee, Cindy H.; Butler, Jason; Spencer, Andrew; Micklethwaite, Kenneth; Li, Jingya; Cusson, Elissa; Bagnall, Robert; Harrison, Simon J. (Frontiers in Oncology, 2025)
BackgroundRegulatory bodies have recently approved chimeric antigen receptor (CAR)-T cell therapies for patients with multiple myeloma (MM), but the treatment process involves complex decision making. To support the introduction of these therapies, we aimed to establish consensus expert opinion on best practices of all aspects of the management of patients with MM undergoing CAR-T cell therapy in Australia.MethodsWe conducted a modified RAND/UCLA two-round Delphi panel informed by a systematic literature review (SLR). The SLR included evidence from clinical practice guidelines, interventional trials, and observational studies for CAR-T cell therapy for patients with MM, to synthesize methodological aspects of CAR-T cell therapy related to patient management. The Delphi panel comprised eight hematologists from across Australia, each with significant experience directly treating patients using CAR-T therapy or referring patients for CAR-T cell therapy. Panelists completed the surveys electronically, and attended a virtual meeting held before the second-round questionnaire to discuss the first-round questionnaire responses. Consensus was defined a priori as at least 70% agreement on survey questions.ResultsThe SLR identified 22 interventional or observational studies and 5 clinical practice guidelines reporting on selection and management of patients with MM treated with CAR-T cell therapy from various global regions. The Delphi panel reached consensus on practices related to patient referral, screening, selection, prioritization, treatments requiring wash-out, bridging therapy, lymphodepletion, infusion, and post-infusion monitoring and management. Most consensus results aligned with consistently recommended practices within guidelines included in the SLR. Consensus was not reached for statements related to specific screening practices and post-treatment monitoring, suggesting differing opinions on the specific best practices to implement.ConclusionOur Delphi panel established expert consensus on key considerations for patient selection, administrative processes, and aftercare for patients with MM in Australia undergoing CAR-T therapy. This will guide the development of clinical practice guidelines which are relevant and feasible to Australian health systems.